Find & search word game for learning english - Leong, Weng Siong (2024)
This project is to develop a gamified learning platform based on Android. This Android game is designed to promote responsible gaming and learning behavior. In this month of increasingly advanced technology, smartphones have become a tool used by almost every household. Online gaming has also become a pastime for most young people, especially with the COVID-19 pandemic. When they can't go out, many people choose to pass the time through online games. Games can not only be used to pass time, but can also be used to learn knowledge or stimulate students' interests. But many teenagers also recharge money in online games in exchange for what they want. In addition, the traditional review method uses rote memorization to make students negative and have a negative attitude towards learning. Therefore, we will achieve responsible gaming behavior and enhance students' enthusiasm for learning by adding interesting gameplay, rankings, notification functions for minors not to recharge, different levels of difficulty, different specific themes, etc.